2020
DOI: 10.21203/rs.3.rs-17231/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shared Decision-making between health care providers and patients at a Tertiary Hospital Diabetic Clinic in Tanzania

Abstract: BackgroundPatients’ participation in decision making regarding their treatment is defined in ethical, legal and human rights standards in the provision of care that concerns health providers and the entire community.ObjectiveTo assess practices and challenges of diabetic patients and healthcare providers’ participation in shared decision making at Muhimbili National Hospital in Dar es Salaam.MethodsThis study employed a phenomenological study design using in-depth interview technique. Study participants were d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 27 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…While the patient -provider power imbalance seems inevitable in clinical encounters, it is a reported drawback for lack of patients' participation (9,10). Due to socio-political predispositions, patients in this study perceive that providers are a superior and unchallenged authority; and that their role should be a subservient, grateful recipient of care.…”
Section: The Non-inviting Atmosphere For Collaborative Dialoguementioning
confidence: 82%
See 4 more Smart Citations
“…While the patient -provider power imbalance seems inevitable in clinical encounters, it is a reported drawback for lack of patients' participation (9,10). Due to socio-political predispositions, patients in this study perceive that providers are a superior and unchallenged authority; and that their role should be a subservient, grateful recipient of care.…”
Section: The Non-inviting Atmosphere For Collaborative Dialoguementioning
confidence: 82%
“…However, it was found that the passivity was related to fear of their providers reaction if they engaged in asking questions. (14) The stated experience highlights a failed therapeutic patient -provider relational ambience where patients do not feel safe enough to contribute or question about their care (10,15).…”
Section: The Non-inviting Atmosphere For Collaborative Dialoguementioning
confidence: 99%
See 3 more Smart Citations